THE CATAWAMPUS CAR - Gordon , Gus
The catawampus cat walks with a slant. And his skewed point of view has everyone in town looking at everything with fresh eyes. Even Bushy Brows Billiam who never notices anything, including what time class is over, spots the catawampus cat, and now he$1 (Bs a star student! And when the town librarian sees the catawampus cat, she pulls the (3z(Bwrong(3y (Bbook from the shelf, sending her into a life of adventure. The catawampus cat is in town and everything is about to change.s
Keywords: illustration